Can Business Grants Mitigate a Crisis? Evidence from Youth Entrepreneurs in Kenya during COVID-19 - Domenella, Yanina (World Bank, Washington, DC, 2021)
COVID-19 was a major shock to youth entrepreneurs and their businesses in Kenya. This paper studies the causal impact of grants—worth two months of baseline business revenue—and business development services as potential mitigation measures. Using multiple rounds of phone surveys up to seven months from the start of the pandemic, the analysis finds that youth who are assigned business grants or a combination of grants and business development services are significantly more likely to maintain a business, earn more revenue and profits, retain employees, and report higher confidence and satisfaction with life. There are no corresponding effects of business development services alone, although the follow-up period is extremely short for training effects to materialize. These results suggest that cash infusion for young entrepreneurs in times of an aggregate shock can be instrumental in moderating its immediate harmful impacts.